2004
DOI: 10.1111/j.0742-2822.2004.02176.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transesophageal Echocardiographic Diagnosis of Left Atrial Myxoma Simulating a Left Atrial Thrombus in the Setting of Mitral Stenosis

Abstract: We report the case of a 56-year-old woman with a history of rheumatic heart disease. The clinical, electrocardiographic, and radiologic findings suggested mitral stenosis. Left atrial obstructive myxoma simulating a thrombus was found by transthoracic echocardiography (TTE). The diagnosis was established by use of transesophageal echocardiography (TEE), confirmed after surgery and by anatomical investigation. Cardiac myxoma associated with mitral stenosis may be difficult to diagnose accurately using TTE. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Distinction between a thrombus and a myxoma in the left atrium is not always straightforward . Left atrial myxomas characteristically appear as round or oval structures containing a mucopolysaccharide myxoid matrix, but they sometimes have a nonhomogeneous appearance, reflecting cystic areas or hemorrhages .…”
Section: Discussionmentioning
confidence: 99%
“…Distinction between a thrombus and a myxoma in the left atrium is not always straightforward . Left atrial myxomas characteristically appear as round or oval structures containing a mucopolysaccharide myxoid matrix, but they sometimes have a nonhomogeneous appearance, reflecting cystic areas or hemorrhages .…”
Section: Discussionmentioning
confidence: 99%
“…While a mass in the LAA is usually a thrombus especially in the setting of atrial fibrillation, myxomas have also been rarely reported 1,2 . The distinction between a thrombus and a myxoma in the LA is not always straightforward and cases of difficulty have been reported 1–3 . Precise diagnosis is important as treatment modalities differ and are not without risk.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid is effective in the treatment of trauma induced coagulopathy and blood loss. [1] We report global left and right ventricular dysfunction after tranexamic acid injection in a patient of polytrauma. A 45-year-old polytrauma patient presented with profuse bleeding from external wounds.…”
Section: Global Left and Right Ventricular Dysfunction After Tranexammentioning
confidence: 92%
“…The few remaining tumors originate from atypical sites such as left or right ventricle and valves. [1][2][3] Although, transesophageal echocardiography is more sensitive, two-dimensional (2D) transthoracic echocardiography (TTE) is usually adequate for diagnosis. Surgical resection of the myxoma is the treatment of choice, with low morbidity and mortality.…”
Section: Anterior Mitral Leaflet Myxoma: a Rare Occurrencementioning
confidence: 99%